Distribution of sources of household air pollution: a cross-sectional study in Cameroon - Miranda Baame Esong; André Pascal Goura; Bertrand Hugo Ngahane Mbatchou; Berenice Walage; Herman Styve Yomi Simo; Romarique Mboumo Medjou; Martial Pianta Sonkoue; Cyrielle Douanla Djouda; Rose Suzie Fowoh Ngnewa; Milaine Sandra Teugueu Guiagain; Brice-Donald Kemnang Agokeng; Olivia Tania Megaptche Homla; et al. (BMC, 2021)
Abstract Background Household air pollution (HAP) is a recognised risk factor for many diseases, including respiratory diseases, cardiovascular/circulatory disorders, adverse pregnancy outcomes and cataracts. Population exposure to biomass fuels, including wood, varies among countries and from one fuel source to the other. This study aimed to investigate the different sources of HAP in peri-urban and rural communities in Cameroon. Methods A cross-sectional survey was conducted in a representative sample of households from the Dschang Health District (DHD) region. This included 848 homes in which a range of fuels for cooking including biomass (firewood, charcoal, sawdust), kerosene and liquefied petroleum gas (LPG) were used both indoors and outdoors. Results Of the study households, 651 (77%) reported exclusive use of firewood and 141 (17%) reported using more than one source of fuel. Exclusive use of firewood was greater in rural communities (94%) than in peri-urban communities (38%). In peri-urban communities, use of multiple fuels including LPG, wood, sawdust and kerosene, was more common (44.75%). A total of 25.03% of households in both peri-urban and rural communities reported using bottled gas (or liquified petroleum gas (LPG) for cooking. Motivations for choice of fuel included, affordability, availability, rapidity, and cultural factors. Conclusion Wood is the main cooking fuel in both peri-urban and rural communities in the Dschang Health District. Supporting households (especially those with limited resources) to adopt LPG equipment for cooking, and use in a more exclusive way is required to help reduce household air pollution.